Cinema's original sin: D. W. Griffith, American racism, and the rise of film culture: by Paul McEwan, Austin, TX, University of Texas Press, 2022, 272 pp., $55.00 (hardcover), ISBN: 978-1-4773-2548-3. - Adamson, Patrick (Early Popular Visual Culture, 2023)
Few films in the history of the medium have been as widely discussed as D. W. Griffith's I The Birth of a Nation i , an infamous Civil War epic routinely cited in debates, both academic and otherwise, about cinema, art and racism since its release in 1915. In a time that saw the emergence of new ideas about "art cinema", his older films continued to be revived both for new commercial endeavours, such as the sound reissue of I The Birth of a Nation i in 1930, and, increasingly, for retrospectives.